T.JUMAMURATOV ShÍǴARMALARÍNDA FRAZEOLOGIZMLERDIŃ STILLIK QOLLANÍLÍWÍ - Allanazarov, E.E.; Xojanova, A.O. (SCIENCE and SOCIETY, 2025)
In the article, one of the linguistic units of our language is devoted to the event of the use of phraseological units in the artistic language. In the works of T. Jumamuratov, some details are given concerning the peculiarities of the meaning of the word in use.